KAJIAN TEOLOGI MORAL TERHADAP FASHION SEBAGAI ISU BUDAYA POPULER - Stella Y. E. Pattipeilohy; Yahya Wijaya (Jurnal Kawistara, 2018)
The focus of this study is fashion as an issue in the discourses on popular culture. Fashion in this case is considered not merely a matter of basic human needs (clothing, eating, and living), but a meaningful cultural “text” and a “sign” of identity politics, moral value change, and spiritual preference. The moral theological response suggested here is the ideology criticism approach promoting the values of authenticity and simplicity, starting from the fashion practice of faithful communities.